Crustal Thickening of the Northern Central Andean Plateau Inferred From Trace Elements in Zircon. Issue 3 (1st February 2022) - Sundell, Kurt E.; George, Sarah W.M.; Carrapa, Barbara; Gehrels, George E.; Ducea, Mihai N.; Saylor, Joel E.; Pepper, Martin
Abstract: The timing of crustal thickening in the northern Central Andean Plateau (CAP), at 13–20°S, and its relationship to surface uplift is debated. Zircon qualitatively records crustal thickness as its trace element chemistry is controlled by the growth of cogenetic minerals and relative uptake of light and heavy Rare Earth Elements. Jurassic to Neogene zircons from volcanic rocks, sandstones, and river sediments reveal shifts in trace element ratios suggesting major crustal thickening at 80–55 Ma and 35–0 Ma, coincident with high‐flux magmatism. An intervening magmatic lull due to shallow subduction obscures the magmatic record from 55 to 35 Ma during which thickening continued via crustal shortening. Protracted thickening since the Late Cretaceous correlates with early elevation gain of the CAP western margin, but contrasts with Miocene establishment of near modern elevation in the northern CAP and the onset of hyperaridity along the Pacific coast, highlighting their complex spatial and temporal relationship. Plain Language Summary: Detailed relationships between crustal thickening, surface uplift, and climate remain unresolved. Although most mountains seem to be in isostatic equilibrium today, there is an imperfect correlation between elevation and crustal thickness in the modern continental lithosphere globally. We report trace element geochemical data of zircons extracted from volcanic rocks, sandstones, and modern river sediments collected in the northern Central Andean Plateau. Our analysis suggests that crustal thickness significantly increased from 80 to 55 Ma and from 35 Ma to present. The magmatic record between these two periods is obscured because the subducting slab shallowed, causing a decrease in magmatic activity; despite this, crustal thickening continued due to crustal shortening. The ∼80 Myr history of crustal shortening correlates with an early phase of surface uplift on the western side of the orogenic system, but contrasts with the main phase of plateau uplift and establishment of hyperaridity along the Pacific coast. Key Points: New zircon trace element data record thin crust at 200–80 Ma and major phases of crustal thickening at 80–55 and 35 Ma to present Thickening at 55–35 Ma is obscured by a magmatic lull due to shallow subduction, during which thickening continued via crustal shortening Results highlight the complex spatiotemporal relationship of late Cenozoic Central Andean crustal thickening, surface uplift, and climate